Evaluation of Women's knowledge about Family Planning Methods at Omer Sawi Teaching Hospital - ali, dr.faiza; Abdalhabfiz, Leila (Iraqi National Journal of Nursing Specialties, 2023)
Objective)s(: This study aimed at evaluating women's knowledge about family planning (FP) methods.Methodology: Descriptive correlational hospital-based research was conducted at Omer Sawi Teaching Hospital, from August to September 2019. A random sample of (320) woman was recruited post their agreement. Data were collected by interview questionnaire and analyzed using a statistical package for social sciences (SPSS) which included the use of descriptive and inferential statistical methods with accepted P < 0.05for the significant correlation. Results: The research findings revealed that the age group between (21-25) year represented (53.1%), most common education level was secondary school (56%). Most of women had (2-5) children. Half of the women had delivered their children with space of less than one year. Knowledge of women about FP was (58.5%). Although, 224(70%) had past experience of FP use, however, over one third 80(35.7%) stopped it because of different reasons, mainly the side effect. Currently, (45%) of the participant used FP, mainly hormonal methods 204(63.74%). Significant correlation was found between women’s knowledge about FP and their educational level (r = 0.768. P = 0.000).Conclusions: Women's knowledge of FP was poor and women focused on the use of hormonal methods. Significant correlation was found between women's knowledge about FP and their educational level. Recommendations: Empowerment of women concerning family planning should be intensified to insure its sustainability over the time.